2022
DOI: 10.1111/mpp.13218
|View full text |Cite
|
Sign up to set email alerts
|

The apple FERONIA receptor‐like kinase MdMRLK2 negatively regulates Valsa canker resistance by suppressing defence responses and hypersensitive reaction

Abstract: Valsa canker, caused by the fungus Valsa mali, is one of the most destructive diseases of apple trees in China and other East Asian countries. The plant receptorlike kinase FERONIA is involved in plant cell growth, development, and immunity. However, little is known about the function of FERONIA in apple defence against V. mali. In this study, we found that MdMRLK2 was highly induced by V. mali in twigs of V. mali-susceptible Malus mellana but not in those of the resistant species Malus yunnaensis. 35S:MdMRLK2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 84 publications
0
10
0
Order By: Relevance
“…To protect apple from freezing damage, it is important to understand better the mechanisms by which it responds to cold stress. In previous studies, we showed that MdMRLK2 ‐OE enhanced apple drought resistance (Jing et al., 2023) but compromised Valsa canker resistance (Jing et al., 2022). In this study, we discovered that MdMRLK2 ‐OE also positively affects apple cold tolerance.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…To protect apple from freezing damage, it is important to understand better the mechanisms by which it responds to cold stress. In previous studies, we showed that MdMRLK2 ‐OE enhanced apple drought resistance (Jing et al., 2023) but compromised Valsa canker resistance (Jing et al., 2022). In this study, we discovered that MdMRLK2 ‐OE also positively affects apple cold tolerance.…”
Section: Discussionmentioning
confidence: 86%
“…“Royal Gala,” was used for apple transformation. Two transgenic lines were obtained: OE‐1 and OE‐2, with 15.2‐ and 19‐fold induction in MdMRLK2 expression, respectively (Jing et al., 2022). Tissue‐cultured “GL‐3” (WT) and MdMRLK2 ‐OE apple plants were sub‐cultured every 4 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…The important region of Fs00367 may be used as a target region for host-induced gene silencing (HIGS)induced breeding. ScPi21 may be used for overexpression or RNAi of ROS (Levine et al, 1994), callose accumulation (Jing et al, 2022) and the high expression of immune genes (Zhang et al, 2021). In our previous study, the full length of Fs00367 was identified to suppress the cell death induced by BAX.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, MdMRLK2 , a FER homologous gene in apple, was found to be highly induced by Valsa mali in the susceptible Malus mellana , but not in the resistant Malus yunnaensis . MdMRLK2 suppressed the hypersensitive reaction by interacting with MdHIR1 and probably impairing MdHIR1 oligomerization (Figure 1 ) (Jing et al, 2022 ). Thus, FER seems to have differential roles in the responses to biotrophic, hemibiotrophic and necrotrophic pathogens.…”
Section: Feronia Controls Ligand‐induced Immune Complex Form...mentioning
confidence: 98%